Entre Contact Zones y Safe Houses : las comunidades étnicas ante el estado-nación argentino - Schierenbeck, Tomás (2021)
Proponemos adaptar los conceptos formulados por Pratt (1991) en Arts of the Contact Zone como herramientas teóricas capaces de analizar las estrategias desplegadas por distintos colectivos étnicos asentados en la ciudad de Buenos Aires entre fines del siglo XIX y principios del XX para acomodarse a las coyunturas políticas de la sociedad porteña. Para esto, exhibiremos, mediante los proyectos educativos de distintas escuelas bilingües y las acciones de la colectividad alemana en la ciudad durante la Gran Guerra, como estas desarrollaron "espacios seguros" donde resignificaban su identidad colectiva sin desvincularse del Estado-nación argentino ni ocultando su componente étnico.
We propose to adapt concepts suggested by Pratt (1991) in Arts of the Contact Zone into theoretical tools capable of revealing how those ethnic groups settled in Buenos Aires between the end of the 19th century and the beginning of the 20th deployed different strategies in order to accommodate themselves to particular political climates in the local society. For this, we will show, through the educational projects of different bilingual schools, as well as in the actions of the German community in the city during the Great War, how they developed "safe spaces" where they redefined their collective identity, all without dissociating themselves from the Argentine nation-state or hiding its ethnic component.
Keywords: Buenos Aires; Contact Zone; Safe House; Colectividades étnicas; Buenos Aires; Contact Zone; Safe House; Ethnic collectives